Arcuate AgRP neurons and the regulation of energy balance - Cansell, Céline; Denis, Raphaël G.; Joly-Amado, Aurélie; Castel, Julien; Luquet, Serge H. (Frontiers in Endocrinology, 2012)
The arcuate nucleus of the hypothalamus contains at least two crucial populations of neurons that continuously monitor signals reflecting energy status and promote the appropriate behavioral and metabolic responses to changes in energy demand. Neurons making pro-opiomelanocortin (POMC) decrease food intake and increase energy expenditure through activation of G protein-coupled receptors melanocortin receptors (MCR) via the release of a-melanocyte stimulating hormone. A prevailing idea until recently was that the neighboring neurons expressing the orexigenic neuropeptides, agouti-related protein (AgRP) and neuropeptide Y (NPY) (AgRP neurons) increased feeding by opposing the anorexigenic actions of the POMC neurons. AgRP neurons activation but not POMC neurons inhibition was recently demonstrated to be necessary and sufficient to promote feeding. AgRP expressing axons were identified in mesolimbic, midbrain and pontine structure where they regulate feeding but also feeding-independent functions such as reward or peripheral nutrient partitioning. Post-synaptic Gamma aminobutyric acid (GABA), lasting in a timeline similar to neuromodulation, was identified as the core mechanism by which hunger-activated neurons regulate feeding and non-food related processes in a melanocortin independent manner.